Transformasi Digital SDM Pengelola Desa Wisata melalui Pelatihan Konten Kreatif dan Strategi Kampanye Digital Marketing - Badie Uddin; Dexi Triadinda; Ferryal Abadi; Puspita Chairun Nisa; Ria Estiana (Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
This community service activity aims to improve the human resource capacity of the Bantaragung Majalengka Tourism Village managers through training in creative content and digital marketing campaign strategies. The method used was Participatory Action Research (PAR), which actively involved participants through the stages of planning, action, observation, and reflection. The activities included training in digital content creation, social media management, and designing digital campaigns based on hands-on practice. Evaluation results showed a significant increase in participant understanding, with an average pre-test score of 58.0 increasing to 80.4 in the post-test, an increase of 38.6%. In addition, participants were able to produce more creative content and began implementing digital marketing strategies independently. The impact of implementation was seen in the increase in the tourism village's social media activity, including the number of posts, user interactions, and follower growth.